2007
DOI: 10.1177/0883073807299857
|View full text |Cite
|
Sign up to set email alerts
|

Subependymal Periventricular Heterotopias in a Patient With Ehlers-Danlos Syndrome: A New Case

Abstract: Ehlers-Danlos syndrome is a complex hereditary connective tissue disorder that is characterized by abnormalities of the skin and joints and visceral and neurological manifestations. At present, at least 11 forms are recognized on the basis of their clinical characteristics, methods of transmission, and biochemical defect. The neurologic manifestations include cerebrovascular disease, peripheral neuropathy, plexopathy, periventricular subependymal heterotopias, and epilepsy. Previously, 2 females were reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Age of onset is also variable from first year of life to adolescence. 47,[72][73][74][75][76] No correlation has been found between the extent and severity of the PH and frequency of seizures. It has been suggested that onset of seizures can begin simultaneously from periventricular heterotopic cortex and from distantly located cortical areas.…”
Section: Eds and Periventricular Heterotopiamentioning
confidence: 84%
“…Age of onset is also variable from first year of life to adolescence. 47,[72][73][74][75][76] No correlation has been found between the extent and severity of the PH and frequency of seizures. It has been suggested that onset of seizures can begin simultaneously from periventricular heterotopic cortex and from distantly located cortical areas.…”
Section: Eds and Periventricular Heterotopiamentioning
confidence: 84%
“…The pathogenesis of neurological manifestations in EDS could be based on the genetic and biochemical anomalies of the connective tissue in this disorder. Some patients affected by epilepsy and EDS presented lesions on brain RMI, particularly PH . It is possible that the nodules, the main lesions of PH, can cause the epileptic manifestations that are present in patients with EDS .…”
Section: Discussionmentioning
confidence: 99%
“…Some patients affected by epilepsy and EDS presented lesions on brain RMI, particularly PH . It is possible that the nodules, the main lesions of PH, can cause the epileptic manifestations that are present in patients with EDS . Sometimes, other brain lesions are associated with EDS, such as polymicrogyria .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations